Passion and combat on a floral stage: a new species of Uvariopsis (Annonaceae) from Monts de Cristal, Gabon, with notes on its unique pollination ecology - Couvreur, Thomas L.P.; Niangadouma, Raoul; Nguimbit, Igor; Paradis, Anne-Hélène; Dagallier, Léo-Paul M.J.; Baudoin-Huit, Lola; Collin, Myriam; Haran, Julien M.; Droissart, Vincent (Plant ecology and evolution, 2025)
Background and aims – Gabon is a major centre of biodiversity. We describe a new species from the tropical plant family Annonaceae: Uvariopsis niangadoumae sp. nov., known from a single population in the Monts de Cristal National Park. Material and methods – Field work was conducted to collect plant specimens and observe floral visitors. Pollen samples were collected and prepared for microscopic analysis. The phylogenetic tree of Uvariopsis was reconstructed using a maximum likelihood method and based on hundreds of nuclear markers. Pollination biology was studied using a DIY camera trap (PICT) placed near a female flower to record floral visitors and their behaviour for one full day. Several flower visitors were collected and identified using DNA barcoding. Key results – Uvariopsis niangadoumae is a tree reaching five metres tall, characterized by strong-scented leaves, few-flowered cauliflorous foul-smelling flowers, and large pollen grains shed in tetrads. The species is endemic to a small area within the Monts de Cristal National Park. Phylogenetic analysis places U. niangadoumae within the “large-leaved clade” species complex with now five taxa. Pollination is diurnal, and the primary pollinator is a rove beetle (Staphylinidae), which uses the female flowers as a mating site, with males fighting for control of the flower. The rove beetles might be attracted by a chemical cue, the foul scent of the flowers, and visual cues, with the inner part of the petals resembling mushrooms. Conclusion – These results emphasize once again the importance of the Monts de Cristal National Park for biodiversity and highlight conservation concerns for the newly described species. The new species is monitored regularly, especially for fruiting individuals, to support ex situ propagation. The Kinguélé Aval project maintains a conservation nursery with 56 species, including 20 individuals of this new species.